1983
DOI: 10.1017/s0263034600000379
|View full text |Cite
|
Sign up to set email alerts
|

A simple theory of magnetic insulation from basic physical considerations

Abstract: Most of the observed features of magnetically insulated transmission lines are derived from the simple considerations of pressure balance and the space-charge flow limit. These include the mean electron drift velocity and the relationship between line voltage and the currents in the positive and negative lines. This voltage-current relationship is compared with experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 8 publications
1
59
0
Order By: Relevance
“…[4], the sheath current obtained in these simulations is larger than 1D models predict. One estimate of the equilibrium sheath current in a constant impedance MITL is [16,30,31] …”
Section: A Cathode Electron Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4], the sheath current obtained in these simulations is larger than 1D models predict. One estimate of the equilibrium sheath current in a constant impedance MITL is [16,30,31] …”
Section: A Cathode Electron Emissionmentioning
confidence: 99%
“…[4]. That work showed that in the limit of cathode electron emission, the load current scales roughly as Z 2 Load [16,22,30,31].…”
Section: Parameter Studies a Operating Parameter Variationsmentioning
confidence: 99%
“…A low MITL impedance is advantageous for a z-pinch IFE system as it minimizes the inductance between the driver and the load; thus, the voltage generated by dI/dt (required to drive the z-pinch) is minimized [15]. The effective impedance of the MITL is described best by the flow impedance Z f , which is a function of both the geometry and the voltage [16][17][18][19][20][21][22][23][24] and is less than the vacuum impedance of the line Z 0 because of the distributed electron current. Additionally, high current resistively heats the electrode surfaces; when the anode surface is heated above T = 400° C [25][26][27][28][29][30], ions are emitted.…”
Section: Recyclable Transmission Line (Rtl) (C L Olson Snl)mentioning
confidence: 99%
“…The difference between I a and I c is the free electron current flowing along the MITL. Based on the theory of Mendel [9], the MITL voltage can be calculated as a function of the anode and cathode currents:…”
Section: B Electrical Diagnosticsmentioning
confidence: 99%